Cemiplimab and diabetic ketoacidosis: a case report of a rare endocrinopathy associated with immune checkpoint inhibitors - Arecco, Anna; Petolicchio, Cristian; Pastorino, Alessandro; Tanda, Enrica Teresa; Vera, Lara; Boschetti, Mara; Cocchiara, Francesco; Maggi, Davide Carlo; Ferone, Diego; Gatto, Federico (Frontiers in Endocrinology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have revolutionised the cancer treatment landscape in the last decades, improving the outcome of several tumours, such as cutaneous squamous cell carcinoma (cSCC). ICIs are antibodies blocking several immune checkpoint pathways, as cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) and programmed cell death 1 (PD-1) with its ligand PD-L1. However, the activation of immune response can cause a broad range of side effects, called immune-related adverse events (irAEs). Endocrine irAEs are mainly represented by thyroid dysfunctions (thyrotoxicosis or hypothyroidism) and hypophysitis, while adrenal insufficiency and diabetes mellitus (DM) are less common. Diabetic ketoacidosis (DKA) is a potential life-threatening presentation of ICI-induced insulin-dependent DM (IDDM). This report presents a rare case of DKA and IDDM secondary to anti-PD-1 antibody cemiplimab therapy, and this is the third described in the literature to date.Case presentationWe describe the case of a 62-year-old female patient with metastatic perianal squamous cell carcinoma who developed DKA and IDDM after the fifth cycle of cemiplimab. Hyperglycemia (1187 mg/dL), metabolic acidosis (pH 7.27) with bicarbonate levels of 11.9 mmol/L, arterial partial pressure of carbon dioxide of 25.7 mmHg with increased anion gap (equal to 25), and hyperketonuria were present. Adequate glycaemic control was difficult to maintain, and intravenously therapy (insulin, sodium bicarbonate, potassium, and fluids) was required for a long time. Subcutaneous basal-bolus insulin treatment was started, but glycaemic control was scarce, also due to the concomitant administration of prednisone for immune-related hepatotoxicity, until the subject’s death.ConclusionThis report underlines the importance of the awareness on endocrine irAEs with ICIs, particularly life-threatening DKA. A baseline assessment of glycemia and glycated hemoglobin is mandatory, and we recommend a close monitoring of glycemic trend over time during ICIs therapy. Patients and their caregivers should be informed and counselled to recognise DKA signs and symptoms.